Embryo drop-out rates in preimplantation genetic testing for aneuploidy (PGT-A): a retrospective data analysis from the DoLoRes study - Wirleitner, Barbara; Hrubá, Martina; Schuff, Maximilian; Hradecký, Libor; Stecher, Astrid; Damko, Adriane; Stadler, Jürgen; Spitzer, Dietmar; Obkircher, Marlene; Murtinger, Maximilian (Journal of assisted reproduction and genetics, 2024)
PURPOSE: To evaluate the decline in transferable embryos in preimplantation genetic testing for aneuploidy (PGT-A) cycles due to (a) non-biopsable blastocyst quality, (b) failure of genetic analysis, (c) diagnosis of uniform numerical or structural chromosomal aberrations, and/or (d) chromosomal aberrations in mosaic constitution. METHODS: This retrospective multicenter study comprised outcomes of 1562 blastocysts originating from 363 controlled ovarian stimulation cycles, respectively, 226 IVF couples in the period between January 2016 and December 2018. Inclusion criteria were PGT-A cycles with trophectoderm biopsy (TB) and next generation sequencing (NGS). RESULTS: Out of 1562 blastocysts, 25.8% were lost due to non-biopsable and/or non-freezable embryo quality. In 10.3% of all biopsied blastocysts, genetic analysis failed. After exclusion of embryos with uniform or chromosomal aberrations in mosaic, only 18.1% of those originally yielded remained as diagnosed euploid embryos suitable for transfer. This translates into 50.4% of patients and 57.6% of stimulated cycles with no euploid embryo left for transfer. The risk that no transfer can take place rose significantly with a lower number of oocytes and with increasing maternal age. The chance for at least one euploid blastocyst/cycle in advanced maternal age (AMA)-patients was 33.3% compared to 52.1% in recurrent miscarriage (RM), 59.8% in recurrent implantation failure (RIF), and 60.0% in severe male factor (SMF). CONCLUSIONS: The present study demonstrates that PGT-A is accompanied by high embryo drop-out rates. IVF-practitioners should be aware that their patients run a high risk of ending up without any embryo suitable for transfer after (several) stimulation cycles, especially in AMA patients. Patients should be informed in detail about the frequency of inconclusive or mosaic results, with the associated risk of not having an euploid embryo available for transfer after PGT-A, as well as the high cost involved in this type of testing.
Keywords: preimplantační diagnóza; Aneuploidy; Female; aneuploidie; blastocysta; retrospektivní studie; genetické testování; Preimplantation Diagnosis; Pregnancy; Humans; ženské pohlaví; Genetic Testing; mužské pohlaví; Male; lidé; Blastocyst; Retrospective Studies; těhotenství